Morphophysiological attributes of AMF inoculated tomato (Lycopersicon esculentum Mill.) ameliorated by resorcinol, biochar and nanobiochar - Sakina Bibi; Rehman Ullah; Tanvir Burni; Zakir Ullah; Jamal Uddin; Mohammad Nur-e-Alam; Mohsin Kazi (Discover Nano)
Abstract Food consumption will rise rapidly as the global population grows over the next several decades. The current agricultural production system cannot solve this challenge, forcing crop growth to experience more adverse conditions. To promote the long-term sustainability of crop production and reduce reliance on excessive agrochemical use, the implementation of integrated nutrient management systems that involve the combination of chemical and biological fertilizers represents an enormous challenge. The experiment aimed to improve tomato plants (Lycopersicon esculentum Mill.) germination, agronomic, and physiological characteristics through seed priming and foliar spraying with resorcinol (0.1 µM/L), biochar (30 mg/L), and nanobiochar (30 mg/L) and inoculation with or without a mixture of arbuscular mycorrhizal fungi (AMF). Physico-chemical characterization of nano-biochar revealed the presence of elements like carbon, oxygen, calcium, and silicon. Spectroscopic analyses confirmed the presence of functional groups and a mix of crystalline and amorphous structures. The surface showed a moderate negative zeta potential with particles averaging hydrodynamic size of around 77 nm.Notably, either alone or in combination with nanobiochar, resorcinol-primed seeds significantly improved tomato seed germination parameters, such as the germination rate index (GRI), emergence energy (EE), coefficient velocity of germination (CVG), final germination percentage (FGP), and seed vigor index (SVI), resulting in a decrease in the mean germination time (MGT) in both the Saaho and Lerica varieties. AMF inoculation and foliar application of biochar and nanobiochar considerably improved shoot (109.57 ± 0.88, 103.00 ± 0.93 cm), and root length (21.89 ± 0.21, 21.40 ± 0.20cm) and leaf area. Furthermore, increases in the biomass of shoots and fruits under fresh and dry conditions were also investigated. Treatment T13 notably boosted the levels of flavonoids (3.54 ± 0.01, 3.36 ± 0.01 mg/g), total phenol (21.23 ± 0.08, 20.31 ± 0.06 mg/g), total protein contents (44.97 ± 0.45, 42.55 ± 0.41 µg/g), total soluble sugar contents (47.97 ± 0.49, 44.88 ± 0.31 µg/g), and anthocyanin contents (0.70 ± 0.00, 0.68 ± 0.00 mg/g) in both Saaho and Lerica tomato varieties compared to the control. The activity of catalase (CAT) and ascorbate peroxidase (APX) exhibited significant increases in response to treatment T13, showing enhancements of (6.93 ± 0.02, 6.84 ± 0.01 units/g) for CAT, and (6.14 ± 0.02, 5.87 ± 0.04 units/g) for APX, respectively. In contrast, proline levels (3.55 ± 0.02, 3.02 ± 0.00 mg/g) declined in both tomato varieties. The present research showed that resorcinol-functionalized nanobiochar has a beneficial influence on germination parameters and that nanobiofertilizer has a synergistic influence on the morphophysiological properties of tomato plants. Graphical abstract